Dominance and marginality in community psychology knowledge production : a critical analysis of published work. - Graham, Tanya Monique (My University, 2014)
The current global formation, characterised by a burgeoning knowledge economy alongside widespread social discontent and economic upheaval, situates the study of knowledge production in the field of community psychology at a timely socio-historical juncture. Community psychology has a long-standing tradition of introspection about its identity, achievements and future direction, established historically through the analysis of published work. This research engages with this tradition, foregrounding the intellectual role and social position of scholars in the field, and the tensions that are collectively evident their work. The study critically appraises the characteristics of published work over a decade with a view to distilling the topics of interest, the preferred methodological choices and the predominant theoretical concerns of the sub-discipline of community psychology. The study employs a mixed methodology to highlight patterns of dominance and marginality in these elements that situates South African scholarship in the field within the global arena. The study presents a content analysis of trends in 2 229 published articles drawn from two local South African journals (South African Journal of Psychology and Psychology in Society) and four international journals (American Journal of Community Psychology, Journal of Community Psychology, Journal of Community and Applied Social Psychology and Journal of Prevention and Intervention in the Community) that were published between 1 January 2000 and 31 December 2009. Among the variables investigated in the quantitative data analysis were constitutive of the authorship characteristics, publication types, topics, theoretical choices, research methods and participant characteristics appearing in published work, including the representation of marginalised groups. The discursive analysis that follows, presents an in-depth reading of selected texts drawn from this dataset though the use of a critical discursive frame to illustrate of how power and the tensions between dominant narratives and marginal positions in community psychology manifest in published work. This serves to foreground contradictions in the identity, values and foci of the field, and some of the discourses implicated in how these disparities are perpetuated. The thesis contends that knowledge production is a contested site where attention to patterns of dominance and marginality reveal how the workings of power can be detected using both quantitative and qualitative analytic methods to investigate the state of published work. Though vastly different in the quantity of publications generated, and the field’s stage of development, the theoretical and methodological features of articles published internationally and in South Africa were remarkably alike. Across both contexts, results showed the prominent use of preventionist, traditional and ecological theories, rather than critical or social perspectives. This reveals the pervasive influence of biomedical epistemologies in the field. Authors were primarily located in academia rather than in applied community contexts. They published empirical articles most often, and showed an affinity for positivist research approaches and the survey method of data collection. The use of a critical paradigm and associated methodological choices, such as discourse analysis, was rare. Most studies did not focus specifically on marginalised groups, although the presence of forms of structural marginality by race, gender and socio-economic status were similarly proportionate across local and international research. Results suggest a persistent neglect of researching specific marginalised groups, such as those socially excluded due to age, HIV status, migration and sexual orientation. Differences across contexts were especially evident in the choice of research topics, rather than approaches used. On the whole, international research has a much greater emphasis on research topics related to child, youth and family development. Findings suggest that disciplinary forces in the field heavily influence the form of articles and their theoretical and methodological features, across local and international research. However, journal topics are more context-sensitive aspects of publications, and reflect local concerns. In addition to publication trends, the thesis identifies several discourses present in published work that show how the field is constructed and its ideological tensions. The thesis considers these findings in view of the power relations they represent and critically reflects on the intrinsic and extrinsic issues at stake in defining the field of community psychology in light of global knowledge production imperatives.
Keywords: Community psychology; Content analysis; Critical psychology; Discourse analysis; Dominance; Journals; Knowledge production; Intellectuals; Marginality; Power; South Africa